Unimas Study Leave Management System - Chong, Yan Yan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Gaining higher level of education certificate is an essential process for lecturer in Universiti Malaysia Sarawak (UNIMA.S) to increase the amount of talented, experienced and skillful lecturers in UNIMAS. The lecturers in UNIMAS are given opportunity to go for further study at Master and PhD (Doctor of Philosophy) level. The unit in charge for application, management and monitoring activities are UCB (Unit Cuti Belajar) and these activities are conducted through manual process with paper records. However, there are various issues with the current method, such as time consuming, inefficient and high cost (in terms of human resource). The proposed system incorporate (I) a web-based system, accessible from any devices that has Internet connectivity, (2)role-based access to differentiate the level of security and activities, (3) a workflow with alerting mechanism, and (4) a complete reporting modules which includes Google Map visualization. The resulting web-system is fully functional and has achieved the project objectives, and has undergone functional and non-functional testing.